Problematika Peserta Didik dalam Pendidikan Agama Islam di Sekolah Dasar - Wahyuni, Putri (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2025)
The aim of this research is to analyze the problems faced by students in religious education at SDN 1 Asrikaton. Using a qualitative approach and case study methodology, data was collected through interviews with school principals, religious education teachers and students, as well as direct observation of learning activities. Research findings show that the main problems students face are lack of motivation, limited learning opportunities, and lack of parental involvement in their children's religious education. In addition, some students have difficulty understanding religious content which is considered difficult and uninteresting. This research aims to provide a general overview of the challenges in religious education in elementary schools and recommendations for improving education to make it more effective and interesting for students.